2010
DOI: 10.1590/s1516-14392010000300008
|View full text |Cite
|
Sign up to set email alerts
|

Heat treatments and thermomechanical cycling influences on the R-phase in Ti-Ni shape memory alloys

Abstract: This article studies changes observed on the R-phase thermoelastic behavior in a near-equiatomic Ti-Ni shape memory alloy. Three kinds of procedures have been performed: different treatments, thermomechanical cycling under constant loading in shape memory helical springs and thermal cycling in as-treated and trained samples. Several heat treatments were carried out to investigate evolution of the R-phase by differential scanning calorimetry (DSC). A heat treatment was chosen on which R-phase is absent. Shape m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…Ti-Ni alloys exhibit particular physical properties such as pre-transformation behaviors and very low elastic anisotropy 1 and they can be used in robotic and actuator applications [2][3][4] . Their martensitic transformation temperatures (M s ) are close to room temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ti-Ni alloys exhibit particular physical properties such as pre-transformation behaviors and very low elastic anisotropy 1 and they can be used in robotic and actuator applications [2][3][4] . Their martensitic transformation temperatures (M s ) are close to room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…When 5 % at. of Cu is added, a linear correlation is achieved, which allows very good control of the position of the actuator [2][3][4][5][6][7][8] . The correlation study of the microstructural evolution during the recovery process after an "amorphization" with mechanical, electrical and thermal properties is important for the applications of Ti-Ni-Cu system, because by controlling the microstructure with the thermomechanical treatment, the mechanical or electrical response of the alloy can be predicted, for example the position of an actuator.…”
Section: Introductionmentioning
confidence: 99%
“…SMS were submitted to 40 thermal cycles under constant shear stress of 35, 70, 105, 135, 170, 200, 235 and 270 MPa in a temperature interval between 25 and 140 °C. The heating and cooling rate was estimated in 10 and 4 °C.min -1 , respectively 4,6,7 . From data acquisitions, the curves of deformation versus temperature and temperature versus number of cycles were plotted.…”
Section: Methodsmentioning
confidence: 99%
“…Other results have proven that the position of the peaks according to the temperature could be affected by thermal and thermomechanical cycling and heat treatments, causing an increase of the temperature of the peak of B2 and an overlapping of both peaks in DSC, even some authors have reported that R-phase transformation could disappear 6,[7][8][9] . When this overlapping of phases takes place, techniques as electrical resistivity variation has greatly helped to identify the R-phase and the sequence of transformation can be followed [10][11] .…”
Section: Fementioning
confidence: 99%
“…In addition to this, measurements of electrical resistance (ER) with temperature have commonly been used to evaluate transformation temperatures of SMAs [14][15] . Moreover, it is known that mechanical properties as Stress-Assisted Two-Way Memory Effect (SATWME) in Ti-Ni alloys are very important for the development of smart actuators manufactured from this special kind of non-conventional material 7 . However, R-phase transformation is not fully beneficial for those applications where a position control is required (e.g.…”
Section: Fementioning
confidence: 99%